Penerapan Bot Frequently Ask Question (FAQ) FILKOM pada Jejaring Sosial Twitter - Atiqo Tuzumah; Eko Sakti Pramukantoro; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Twitter is one of the popular social networks where short message communications (called tweets) have attracted large numbers of users. Popularity and openness twitter structure has attracted large number of automated programs called bots. Bots is automatic programs designed to simulate conversations, either being similar like human or pure information. Pure information bot is bot that the existence intended to provide information to user. This research automatic notification is applied to reply to the questions frequently asked FILKOM coolege students about FILKOM in the form of FILKOM FAQ. FILKOM FAQs bot-based system that are applied to twitter social networks are easier to access, quicker, and interactive responses. The exchange of information that occurs between the webserver-bot system-and the users / students is done on a scheduled basis.